DETEKSI KESEHATAN KEUANGAN PERUSAHAAN DENGAN MENGGUNAKAN MODEL TAFFLER PADA SUB SEKTOR TEKSTIL DAN GARMEN - Mukti, Chitra; Ridhovan, Andreanov; Damayanti, Alia Sri; Permatasari, Wan Variani; Rosdiana, Rosdiana; Ramadhan, Yanuar (Balance : Jurnal Akuntansi dan Bisnis, 2023)
ABSTRACTThis study aims to detect the financial health of companies that are included in the textile and garment sub-sector and are listed on the Indonesia Stock Exchange (IDX) using the Taffler model using financial report data for the period 2020 - 2022. Through analysis of company financial data in recent years, this study will identify important factors that affect the financial health of companies. The Taffler model will be used to combine financial and other factors in evaluating a company's financial health and identifying potential indicators of bankruptcy. The results of this study are expected to provide a reference for companies in making strategic decisions to maintain financial stability and increase the competitiveness of companies in the textile and garment sub-sector. In this study, the Taffler model predicts that 5 out of 15 companies will go bankrupt in 2023 and 2024.